The Effect of Perceived Justice on Customer Complaint Behavior - Zebeib, Mayan (2006)
In recent years many companies have started to realize the importance of customer satisfaction and effective complaint handling strategies. The marketing literature contains numerous studies that provide insight on the relationship between these two factors. Using perceived justice theory as a conceptual foundation, the current research explains how customers evaluate service failures and recovery encounters, and how these evaluations have an impact on customer satisfaction and negative word-of-mouth. The first section of the research includes an extensive literature review followed by the development of a questionnaire. Respondents were asked to refer to a given scenario that describes a common service failure with an airline company. Then respondents were asked to answer a set of structured questions that were used later to test the impact of perceived justice on customer satisfaction and negative word-of-mouth. The results of the research provide empirical support for the proposed conceptual framework suggesting that perceived justice evaluations play an important role when evaluating service failures and recovery encounters from the customer's point of view.